Decision making in the Council of Ministers of the European Union - Cross, James (Trinity College (Dublin, Ireland). Department of Political Science, 2011)
This thesis examines legislative decision making in the European Union with a specific focus upon decision making in the Council of Ministers. It examines the manner in which member states seek to influence the legislative process at different levels of negotiation within the Council. The first empirical contribution of the thesis (Chapter 4) has two aims. It first examines the influence that legislative rules and procedures have upon the legislative process. It elaborates upon a one-dimensional procedural model of EU politics that explicitly captures the structure of the legislative game by accounting for the order in which actors move, and the manner in which the order of the game affects each actor's ability to influence legislative outputs.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin.